Effect of Vitamin E on in Vitro Sperm Activation of Asthenospermic Infertile Patients by using Swim-up technique - F.Al-Shimerty, Dhirgam; N.Alwachi, Sabah; Al-sultani, YahiaK (Al-Qadisiyah Journal of Pure Science, 2018)
This Study was performed on 50 seminal fluid samples belongs to 50 patients suffering from Asthenospermia The objective of the persent study is to activation patient sperms quality in vitro by using swim-up technique for 30 minute of incubation in Earl’s medium and Earl’s medium + vitamin E to find out the effect of vitamin E on the sperms parameter. The result of sperm patients suffering from Ashenospermia by using the swim-up technique (Earl’s media and Earl’s media + vitamin E) showed that there was a significant decrease (P<0.05) in sperm concentration and leukocyte concentration in comparison to that used before activation. The sperm activation of patients suffering from Asthenospermia by using the swim-up technique (Earl’s media and Earl’s media + vitamin E) showed that there was a significant improvement (P<0.05) in the sperm motility percent, normal sperm morphology percent and sperm grade activity in comparison to its result befor activation Also, a significant improvement was noticed(P<0.05) in the sperm motility percent, sperm grade activity by using swim-up technique when Earl’s media was mixed with vitamin E in comparison to the process of activation in swim-up technique when only Earl’s media was used. However, there was a significant improvement (P<0.05) in sperm concentration swim-up technique by using Earl’s media and vitamin E when compared to that in which only Earl’s media was used. It was concluded that using a human sperm activation it was found that the addition of vitamin E to Earl’s media improve the sperm parameters and their activation in infertile patients suffering from Asthenospermia.